2016
DOI: 10.1016/j.cyto.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Toll/IL-1 domain-containing adaptor inducing IFN-β (TRIF) mediates innate immune responses in murine peritoneal mesothelial cells through TLR3 and TLR4 stimulation

Abstract: Mesothelial cells are composed of monolayer of the entire surface of serosal cavities including pleural, pericardial, and peritoneal cavity. Although mesothelial cells are known to express multiple Toll-like receptors (TLRs) which contribute to trigger innate immune responses against infections, the precise molecular mechanism remains still unclear. In the present study, we investigated the role of Toll/IL-1 domain-containing adaptor inducing IFN-β (TRIF), one of the two major TLRs-adaptor molecules, on innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
1
12
0
2
Order By: Relevance
“…Kato et al (2004) demonstrated constituent expression of Toll-like receptors (TLR) 1-6, CD14, and MD-2 (required for TLR-4 signal transduction) ( Kato et al, 2004 ). Other authors have reached similar results, proving expression of TLR-1 ( Colmont et al, 2011 ), TLR-3 and TLR-2 ( Park et al, 2007 ; Colmont et al, 2011 ; Hwang et al, 2016 ), TLR-4 ( Park et al, 2007 ; Colmont et al, 2011 ; Wang J. et al, 2013 ; Hwang et al, 2016 ), TLR-6 ( Colmont et al, 2011 ), and TLR-5 ( Park et al, 2007 ; Colmont et al, 2011 ). Other receptors like nucleotide-binding oligomerization domain (Nod)-1 and Nod-2 ( Park et al, 2007 ), and AGE receptors (RAGE) ( Boulanger et al, 2002 ) have been identified.…”
Section: Resultssupporting
confidence: 60%
“…Kato et al (2004) demonstrated constituent expression of Toll-like receptors (TLR) 1-6, CD14, and MD-2 (required for TLR-4 signal transduction) ( Kato et al, 2004 ). Other authors have reached similar results, proving expression of TLR-1 ( Colmont et al, 2011 ), TLR-3 and TLR-2 ( Park et al, 2007 ; Colmont et al, 2011 ; Hwang et al, 2016 ), TLR-4 ( Park et al, 2007 ; Colmont et al, 2011 ; Wang J. et al, 2013 ; Hwang et al, 2016 ), TLR-6 ( Colmont et al, 2011 ), and TLR-5 ( Park et al, 2007 ; Colmont et al, 2011 ). Other receptors like nucleotide-binding oligomerization domain (Nod)-1 and Nod-2 ( Park et al, 2007 ), and AGE receptors (RAGE) ( Boulanger et al, 2002 ) have been identified.…”
Section: Resultssupporting
confidence: 60%
“…NF-κB also plays an essential role in innate immune response and many signaling pathways are associated with NF-κB 33 36 37 38 . In previous studies, TRIF mediated innate immune responses in peritoneal mesothelial cells through TLR3 and TLR4 stimulation via activation of NF-κB or MAPKs 39 . Hepatitis C virus NS3 mediated microglial inflammation via TLR2/TLR6-MyD88/NF-κB pathway 40 .…”
Section: Discussionmentioning
confidence: 92%
“…Previous work indicated that inducible nitric oxide synthase (iNOS) (nitric oxide synthase 2) is absent and NO synthesis is totally impaired in TRIF-deficient murine peritoneal cells stimulated with poly(I·C) or LPS (22). There is also evidence that TRIF participates, not only in NO production, but also in the induction of reactive oxygen species (ROS) by macrophages via TLR3 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ability of the TLR3-TRIF pathway to induce IFN-␣ and IFN-␤, here, we have confirmed this mechanism in the Neospora model. Many examples of this induction may be found in the literature: in a study that used mesothelial cells, which act as a protective barrier against invasive pathogens, it was observed that stimulation with poly(I·C), a TLR3 agonist, induced the expression of IFN-␤ mRNA in WT cells; however, this induction was significantly reduced in TRIF-deficient cells (22). In other infection models, such as the bacteria Listeria monocytogenes and Chlamydia muridarum, it has been observed that macrophages deficient in TRIF also present impaired IFN-␤ expression, demonstrating again the strict relationship of the adapter molecule to the cytokine (25,26).…”
Section: Discussionmentioning
confidence: 99%